The Ultraviolet-Visible Luminescence of Ce3+ in Ca2Mg(BO3)2 Phosphors with Potential Applications - Zhang, Jing-Xiang; Lin, Yanru; Lin, Huihong (Journal of Spectroscopy, 2023)
New phosphors Ca2Mg(BO3)2: Ce3+ were synthesized by the solid-state reaction method at a high temperature. The phase purity was characterized by powder X-ray diffraction (XRD). The ultraviolet-visible (UV-Vis) optical properties of Ce3+ have been investigated, and the lowest 5d levels, the emission, and the Stokes shifts of Ce3+ in the host lattice were identified. In addition, its concentration quenching process was also studied. The results show that Ce3+ ions enter Ca2+ sites with only one emission in a UV-Vis range and that the optimum doping concentration is x = 0.05. The excitation and emission spectra were evaluated to clearly reveal luminescence features.